Degradation during processing in poly(butylene adipate-co-terephthalate)/vegetable fiber compounds estimated by torque rheometry. (October 2016) - Almeida, Tatiara G.; S. Neto, João Emídio; Costa, Anna Raffaela M.; da Silva, Aline S.; Carvalho, Laura H.; Canedo, Eduardo L.
Abstract: The effect of filler type and concentration on the rate of degradation of poly(butylene adipate- co -terephthalate)/vegetable fiber compounds was studied using a convenient and sensitive procedure based on torque rheometry, which was used for the quantitative estimate in real time of incipient degradation during melt processing in polymer systems. It was found that the presence and level of two filler types, taken from two different layers of the fruit of the babassu palm tree, greatly enhance the slight degradation tendency of the matrix when processed in a laboratory internal mixer. The qualitative trends and quantitative estimates may be explained by the chemical and morphological characteristics of the two fillers, as observed by optical microscopy.